Understanding the potential scope, definition and impact of the WTO e-commerce Moratorium - Andrenelli, Andrea (OECD Publishing, 2023)
New empirical evidence and analysis of provisions in regional trade agreements help bring clarity to debates on the potential scope, definition and impact of the WTO e-commerce Moratorium. OECD analysis demonstrates that the potential fiscal revenue implications of the Moratorium are small, amounting to, on average, 0.68% of total customs revenue or 0.1% of total government revenue. Well-designed value added or goods and services taxes (VAT/GST) can help offset potential foregone revenue in most countries. Failure to renew the Moratorium would result in greater policy uncertainty and less trade, and tariffs on electronic transmissions would reduce domestic competitiveness. Adverse effects would be most pronounced for low-income countries and smaller firms. Overall, evidence demonstrates that there is a strong case for the Moratorium to be renewed
Keywords: Trade